The Effect of Infant Massage on the Duration of Breastfeeding in Infants at Independent Midwife Practice Hutri and Independent Midwife Practice Nur Asmalindar - Bancin, Fitriani; Amra, Ricca Nophia; Harahap, Asrika Sari (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
Infant massage is a form of tactile stimulation that has been proven to provide physiological and psychological benefits, especially in supporting successful breastfeeding. This study aims to determine the effect of infant massage on the duration of breastfeeding in infants at Hutri Independent Midwife Practice and Nur Asmalindar Independent Midwife Practice. The research design used was a quasi-experiment with a Non-Equivalent Control Group approach. The sample consisted of 30 infants divided into two groups, namely the intervention group (infant massage) and the control group (without massage), each consisting of 15 respondents. Data were analyzed using the Wilcoxon test. The results showed that before the intervention, 43.3% of infants in the massage group had a short breastfeeding duration and none of them breastfed for a long duration. After the massage was given, 93.3% of infants increased to the long breastfeeding duration category. Conversely, in the group without massage, only 6.7% of infants breastfed for a long duration. The Wilcoxon test showed a p value = 0.000 in the massage group and p = 0.042 in the group without massage, which means there was a significant difference. These results suggest that infant massage can be an effective intervention in increasing infant breastfeeding duration.